2019
DOI: 10.1158/1535-7163.mct-18-0804
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Notch1 Activity Inhibits Prostate Cancer Growth and Metastasis and Sensitizes Prostate Cancer Cells to Antiandrogen Therapies

Abstract: Prostate cancer remains among the leading causes of cancerrelated deaths in men. Patients with aggressive disease typically undergo hormone deprivation therapy. Although treatment is initially very successful, these men commonly progress to lethal, castration-resistant prostate cancer (CRPC) in 2 to 3 years. Standard therapies for CRPC include second-generation antiandrogens, which prolong patient lifespan by only several months. It is imperative to advance our understanding of the mechanisms leading to resist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 53 publications
2
40
0
Order By: Relevance
“…These ndings suggest that elevated KLK8 may exert the pro-proliferation and anti-apoptotic effects in pancreatic cancer cells through activating PI3K-Akt-mTOR signaling pathway. Notch signaling pathway also plays an important role in the occurrence and progression of pancreatic cancer [40][41][42]. In the present study, GSEA analysis and western blot assay revealed that KLK8 overexpression resulted in the activation of Notch signaling pathway.…”
Section: Discussionsupporting
confidence: 53%
“…These ndings suggest that elevated KLK8 may exert the pro-proliferation and anti-apoptotic effects in pancreatic cancer cells through activating PI3K-Akt-mTOR signaling pathway. Notch signaling pathway also plays an important role in the occurrence and progression of pancreatic cancer [40][41][42]. In the present study, GSEA analysis and western blot assay revealed that KLK8 overexpression resulted in the activation of Notch signaling pathway.…”
Section: Discussionsupporting
confidence: 53%
“…MAOAI is also in clinical trial for non-metastatic PC clinical trials (NCT02217709). Finally, inhibitors of gamma secretase which regulates cleavage of cell surface receptors including Notch receptors among others, in combination with enzalutamide or abiraterone in vitro inhibits PC cell growth, migration and invasion, as well as sensitizes enzalutamide resistant cells and xenografts to enzalutamide treatment (116119).…”
Section: Resistance and Combination Therapy Strategiesmentioning
confidence: 99%
“…Aside from breast cancer, lung cancer, ACC and possibly colorectal cancer, cell-autonomous activating Notch mutations in solid tumours are less common than haematological cancers. However, upregulation of wild-type Notch receptors and ligands, and aberrant Notch signalling is frequently observed in various tumours including melanoma [ 86 ], gastric cancer [ 87 ], ovarian cancer [ 88 ], prostate cancer [ 89 , 90 ], pancreatic cancer [ 91 , 92 ], hepatocellular carcinoma [ 93 , 94 , 95 ], glioma [ 40 , 96 , 97 ] and rare tumours such as cholangiocarcinoma [ 98 ] and desmoid tumours [ 99 ]. Notch gene alterations may play a role in a subset of these cancer cases; however, such mutations are yet to be identified.…”
Section: Notch In Cancer: An Overviewmentioning
confidence: 99%
“…Androgen deprivation therapy (ADT) with the use of AR antagonists such as enzalutamide is standardly used in the treatment of late-stage and metastatic prostate cancer and similar to ER antagonists, it is associated with a short response period and subsequent drug resistance [ 90 , 150 ]. A recent study has indicated that Notch 2 is overexpressed in enzalutamide-resistant prostate cancer patients, while cleaved or activated Notch 1 and HES-1 levels were increased in enzalutamide-resistant cell line models [ 219 ].…”
Section: Notch Crosstalk With Other Signalling Pathways and Therapmentioning
confidence: 99%
See 1 more Smart Citation